Natural variability masks climate change sea surface temperature signals: a comparison between the Baltic Sea, North Sea and North Atlantic Ocean - H. Mashayekh Poul; M. Gröger; S. Karsten; B. Mayer; T. Pohlmann; H. E. M. Meier (Climate Dynamics, 2025)
Climate variability in marine environments, particularly sea surface temperature (SST), is influenced by natural fluctuations occurring at various temporal and spatial scales. Distinguishing between anthropogenic climate change trends and natural variability is crucial for understanding the complex dynamics of ocean temperatures. This study applies the concept of Time of Emergence (ToE) to estimate when the signal of long-term climate change becomes distinguishable from natural variability in SST for different seasons. The study focuses on the North Sea, Baltic Sea, and North Atlantic Ocean, utilizing 30 ensemble members of simulation from a regional climate model system, MPIOM-REMO, with slightly different initial conditions. The results reveal that winter ToEs emerge earlier than summer ToEs in all study areas, mainly driven by larger winter SST changes and show that shallow coastal seas like the North and Baltic Seas experience earlier ToEs than the deep central North Atlantic. These findings emphasize the influence of regional processes, such as sea ice dynamics and changes in stratification, on the spatial and temporal variability of ToE patterns.

Distribution and diel vertical migration of mesopelagic fishes in the Southern Sargasso Sea — observations through hydroacoustics and stratified catches - L. Marohn; M. Schaber; M. Freese; J. D. Pohlmann; K. Wysujack; S. Czudaj; T. Blancke; R. Hanel (Marine Biodiversity, 2021)
Vertical distribution patterns and relative abundance of mesopelagic fish species and other major taxonomic groups were investigated through vertically stratified trawl sampling and hydroacoustic analyses along the subtropical convergence zone from 52° W to 70° W in the oligotrophic Sargasso Sea. Persistent stationary layers and several migrating components of different scattering characteristics were detected. The results reveal varying vertical migration patterns, including different times of onset of diel vertical migration in different depths and a migrant pathway emerging daily from the lower deep scattering layer (DSL) at dusk and migrating through the upper DSL without affecting its composition. Fish species identification was made based on morphological characteristics and confirmed by genetic barcoding analyses of subsamples. In total, 5022 fish specimens from 27 families, 62 genera and 70 species were caught. In terms of relative abundance (A) and biomass (M), catches were dominated by species of the families Myctophidae (A=59.1%, M=47.4% of total fish catch) and Melamphaidae (A=22.5%, M=17.1%). Myctophidae and Stomiidae were the most species-rich families with 31 and 12 species, respectively. Catches at the two easternmost stations were dominated by Scopelogadus mizolepis and Nannobrachium cuprarium, while Bolinichthys photothorax and Ceratoscopelus warmingii were the most abundant species in catches from the two westernmost stations. This study provides insights into distribution and vertical migration behaviour of mesopelagic fish in the Sargasso Sea and adds to our understanding of the mesopelagic community in this large oceanic area.

The atmospheric impact on fluxes of nitrogen, POPs and energy in the German Bight - M. Schulz; J. Beusekom; K. Bigalke; U. Brockmann; W. Dannecker; H. Gerwig; H. Grassl; C. -J. Lenz; K. Michaelsen; U. Niemeier; T. Nitz; E. Plate; et al. (Ocean Dynamics, 1999)